Parametric Amplification/Mixing Using the Varactor Diode - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components)
This paper deals with the large-signal analysis of parametric amplification/mixing using reverse biased p-n junction varactor diodes. Expressions are obtained for the current components of the parametric amplification/mixing. The special case of relatively small input amplitudes is considered and the results are compared with previously published results.